Molecular Characterization, Gene Expression and Antibacterial Activity Analysis of a Novel Piscidin (Piscidin-4) of Largemouth Bass (Micropterus Salmoides) - Jingyun Tian; Liqiang Zhang; Qihuan Zhang; Yang Xu; Xuan Wei; Mingzhu Pan; Zisheng Wang; Zhitao Qi (Fishes, 2026)
Piscidins, fish-specific antimicrobial peptides (AMPs), play important roles in the innate immunity of fish against invading bacteria. In this study, a novel piscidin was identified in largemouth bass (Micropterus salmoides) (MSPiscidin-4), which contained an active peptide of 25 aa with an amphipathic helix possessing distinct hydrophobic and positively charged regions. MSPiscidin-4 belongs to the Group I piscidins as determined by sequence identity, homology modeling and phylogenetic tree analysis. MSPiscidin-4 was constitutively expressed in all seven selected tissues, with the highest transcript level in the gill and the lowest in the brain and spleen. Furthermore, MSPiscidin-4 was significantly up-regulated in spleen from 6 h to 24 h post-lipopolysaccharide (LPS) stimulation. A synthetic MSPiscidin-4 peptide was produced by the Fmoc solid-phase synthesis method and exhibited antibacterial activity against several aquatic bacterial strains, with the strongest against Aeromonas hydrophila, followed by Vibrio splendidus, Staphylococcus aureus, Edwardsiella tarda, and the weakest against E. coli and A. veronii. MSPiscidin-4 is the fourth piscidin reported in largemouth bass, showing distinct sequence identity (35.0–68.0% with previously reported MSPiscidins), physicochemical properties (net charge +5, pI 12.48), tissue distribution (highest expression in gill), and antibacterial potency (particularly strong against A. hydrophila). Our results enrich the piscidin components and deepen the understanding of piscidins against invading bacteria in largemouth bass.